OVERCOMING CHILDREN'S CREATIVITY CRISIS: INNOVATIVE MEDIA TRANSFORMATION LOOSE PARTS IN OPTIMIZING FINE MOTORCYCLE IN EARLY CHILDREN - Widat, Faizatul; L Muna, Husna (FORUM PAEDAGOGIK, 2024)
This research aims to explore the effectiveness of innovative loose parts media in optimizing fine motor skills of young children. Using qualitative methods with a case study approach, this research focuses on how the use of loose parts can stimulate creativity and improve children's fine motor skills. Qualitative research methods were applied to gain an in-depth understanding of the application of loose parts and their impact on child development. Data was collected through direct observation of classroom activities, interviews with educators and parents, and analysis of documents related to loose parts-based activities. Observations were conducted to assess children's interactions with loose parts and progress in fine motor skills, while interviews provided insight into educators' and parents' perceptions and experiences regarding the use of loose parts. The research results show that loose parts media makes a significant contribution in improving children's fine motor skills, such as hand-eye coordination and finger dexterity, as well as stimulating their creativity and imagination. Educators reported increased children's motivation and engagement, while parents noted positive progress in children's fine motor skills at home. This research confirms that loose parts are an effective tool in early childhood education, offering an innovative and practical approach to addressing challenges in the development of creativity and fine motor skills.